FORMULA METHOD FOR ECONOMIC VALUATION OF URBAN FOREST - Arantes, Bruna Lara; Abreu, Rafaela Novaes; Silva Filho, Demóstenes Ferreira da (REVISTA DE AGRICULTURA, 2019)
Trees in urban settings provide several benefits and the value of these benefits is calculable. Urban forest economic valuation has been increasingly applied to facilitate and justify expenditures, more efficiently manage trees, serve as a tool to define costs and benefits, adjust project priorities and policies, and assign a value to environmental impacts. This study was designed to evaluate urban forest samples in two of the city of São Paulo’s administrative districts, Itaim Paulista and Nossa Senhora do Ó, and propose improvements to the existing formula method used to evaluate these assets. The two districts’ tree components are currently valued at US$ 85,165.51 and US$ <span style="font-size: 12pt; line-height: 150%; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">66,814.838, have a m2 valuation of US$2.71 and US$ <span style="font-size: 12pt; line-height: 150%; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">2.12 respectively. Applying the developed formula showed that the formula improvements did differences in these values in 51%. It is recommended that this new formula method should be considered as a new model for urban forest valuation research. Trees in urban settings provide several benefits and the value of these benefits is calculable. Urban forest economic valuation has been increasingly applied to facilitate and justify expenditures, more efficiently manage trees, serve as a tool to define costs and benefits, adjust project priorities and policies, and assign a value to environmental impacts. This study was designed to evaluate urban forest samples in two of the city of São Paulo’s administrative districts, Itaim Paulista and Nossa Senhora do Ó, and propose improvements to the existing formula method used to evaluate these assets. The two districts’ tree components are currently valued at US$ 85,165.51 and US$ 66,814.838, have a m2 valuation of US$2.71 and US$ 2.12 respectively. Applying the developed formula showed that the formula improvements did differences in these values in 51%. It is recommended that this new formula method should be considered as a new model for urban forest valuation research.